Enhancing Kinesthetic Intelligence in Children Between The Ages of 5-6 Through Yapong Traditional Dance - Sari, Diah Andika; Nurfitriah, Siti (Journal of Islamic Education Students (JIES), 2024)
Kinesthetic Intelligence is one of the Multiple intelligences related to children's motor development. In group B class, Bintang Mulia Kindergarten, Bintaro, South Jakarta, still many children not being able to jump on alternate legs, spin or somersault, swing, walk with various variations, or stand on tiptoes with one or two legs. This research aimed to improve kinesthetic intelligence in 12 children aged 5-6 years through traditional Yapong dance. Traditional dance is a form of activity that involves the motor development of early childhood. Yapong dance is a traditional Betawi dance which involves walking with various variations, varying on tiptoes on one and two feet, making turns, and eye and hand coordination. The research method used classroom action research, by the Kemmis & McTaggart model. The results of the research showed that the kinesthetic intelligence of children aged 5-6 years were not initially developed in the pre-cycle with an achievement of only 30%. After getting action in cycle I, it started to grow to 41%. There was an increase to develop according to expectations at 62% in cycle II, and develop very well at 85% in cycle III. There was a significant increasing in the kinesthetic intelligence of children aged 5-6 years after took Yapong Traditional Dance activities for 3 weeks in 10 meetings.┬á